Healthcare professionals’ standard of care during Covid-19 pandemic - Haniwarda Yaakob,; Tengku Noor Azira Tengku Zainudin,; Mohd Zamre Mohd Zahir, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Since the beginning of the year 2020, Malaysia has been gravely affected by the COVID-19 pandemic where to date over four million of its population have been infected with the virus. At the time of writing this paper, the number of infections is still alarming. This situation undoubtedly places a strain on the healthcare system, particularly on healthcare professionals who have been entrusted to treat COVID-19 patients. Treating a high number of patients in an unprecedented situation may pose a challenge for doctors to fulfil their legal duties that arise from the usual doctor-patient relationship particularly in discharging the established standard of care imposed by the law. This is the main issue that this paper seeks to explore. In addition, this paper also examines doctors’ duty of care towards non-COVID-19 patients amidst limited medical resources and policy consideration that inevitably causes a delay in giving medical treatments and elective surgeries. In answering these questions, the method employed in this paper is qualitative analysis. In conclusion, it is suggested that keeping up to the established standard of care is crucial in maintaining public confidence in the medical profession and also to protect public health and welfare.